Community Nurses' Perspective on Barriers to Effective Utilization of Advance Care Planning for Terminal Care of The Elderly in The Home Environment in Japan: A Systematic Review and Synthesis of Qualitative Studies - Yumi Naito; Yoko Tomita; Katrina Breaden; Yvonne Parry (International Journal of Advanced Health Science and Technology, 2022)
Advance care planning (ACP) allows individuals to plan the health care which dignifies their personal values at the terminal phase of their illnesses. The Japanese government previously endorsed the concept of ACP in the guideline on end-of-life care and community nurses in Japan could play an increased role to improve its utilization by patients. The current study aimed to identify challenges surrounding ACP practice in the home environment in Japan from the community nurses’ perspectives. Semi-structured interview was performed on eleven community nurses working in metropolitan areas in Japan. Qualitative data was collected and analyzed using Braun & Clarke’s six-step framework of thematic analysis (2006). Five themes were identified as barriers to effective ACP utilization: complexity surrounding family power, informed consent and discussion, cultural influence, longer life versus better life, and absence of frameworks and guidelines. The first three themes were further subdivided into subthemes: imbalance in family power and family guilt, inadequate information for decision-making and ‘no one talk about it’, and traditional ways of thinking and taboo surrounding talking about death, respectively. The identified issues surrounding the current ACP practice in Japan were interconnected and reflective of the social, cultural, legal, and ethical aspects of life and care in Japan. This study highlighted the importance of respecting patients’ preferences in care, which should be additionally protected by establishing clear policy and legal frameworks on ACP